Weighing neutrinos in dynamical dark energy models - Zhang, Xin (Science China. Physics, mechanics & astronomy, 2017)
The discovery of neutrino oscillation indicates that neutrinos have masses and each flavor state is actually a superposition of three mass states with masses m1,m2,and m3.However,the neutrino oscillation experiments are not able to measure the absolute masses of neutrinos,but can only measure the squared mass differences between the neutrino mass eigenstates—The solar and reactor experiments gave